2004
DOI: 10.1002/adma.200490022
|View full text |Cite
|
Sign up to set email alerts
|

Semiconductive Polymer Blends: Correlating Structure with Transport Properties at the Nanoscale (Adv. Mater. 2004, 16, 385.)

Abstract: To view the original paper click

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
48
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 42 publications
(54 citation statements)
references
References 0 publications
6
48
0
Order By: Relevance
“…[2] Despite the ubiquitous use of PEDOT:PSS, relatively little attention has been given to the basics of the charge transport in this material. [3,4] The lateral conductivity of PEDOT:PSS blends has been addressed for various compositions with variation of pH, [3] solvents, [5] and water content. [6] From the observed temperature dependence, it was concluded that lateral electric conductivity occurs via hopping of charge carriers.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…[2] Despite the ubiquitous use of PEDOT:PSS, relatively little attention has been given to the basics of the charge transport in this material. [3,4] The lateral conductivity of PEDOT:PSS blends has been addressed for various compositions with variation of pH, [3] solvents, [5] and water content. [6] From the observed temperature dependence, it was concluded that lateral electric conductivity occurs via hopping of charge carriers.…”
mentioning
confidence: 99%
“…[7] A recent conductive atomic force microscopy (AFM) experiment on 1 lm thick drop-cast PEDOT:PSS films suggests that the charge transport perpendicular to the substrate is dominated by spacecharge effects, in striking contrast to the transport parallel to the substrate. [4] For the use in pixilated displays, the issue of in-versus out-of-plane anisotropy is of utmost importance since in-plane conductivity causes crosstalk between neighboring pixels, whereas the out-of-plane conductivity has a direct effect on the contact resistance. The currently accepted morphology of spin-cast PEDOT:PSS films is that of a phase segregated material consisting of PEDOT:PSS grains surrounded by a shell formed by excess PSS.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Kemerink and coworkers studied PEDOT:PSS surfaces using STM, [15,16] while both Carter and coworkers [17] and our group [18] studied PEDOT:PSS surfaces using c-AFM (Fig. 1c).…”
Section: Variations In Local Charge Transport Probed With Conductive Afmmentioning
confidence: 98%
“…The C(S)-AFM technique is used in many research fields. It is applied to correlate structure with charge-transport properties in semiconductive blends [82] or polyaniline thin films, [83] and to understand the influence of solvent on conductivity of polythiophenes, [84] or the bioactivity of enzymecontaining polymer structures [85] as well as to measure local electrical properties of inorganic materials such as CdTe/CdS as used for solar cells. [86] Other interesting operating modes of C(S)-AFM are electrical force microscopy (EFM), [87] which was applied to, for example, pentacene monolayer islands, [88] polythiophene (P3HT) thin films, [89] and BaTiO 3 nanowires; [90] scanning Kelvin probe microscopy (SKPM) [91] or scanning surface potential microscopy (SSPM), [92] as used to characterize Nbdoped SrTiO 3 , which finds its application in various research fields such as superconductivity and magnetoresistivity; [93] and scanning capacitance microscopy (SCM) [94] of CNTs and other nanofibers.…”
Section: Electrical Propertiesmentioning
confidence: 99%